Labour productivity: The forgotten yield gap - Cock, James H.; Prager, Steven D.; Meinke, Holger; Echeverria, Ruben (Elsevier, 2022)
Crop yields and labour productivity have increased markedly over the past 70 years. In agriculturally advanced countries, increases in labour productivity – that is, increases in the economic output per unit of labour input – have been several-fold greater than corresponding increases in yield. The gap in labour productivity between the Global North and the Global South is now much greater than the yield gap. This large labour productivity gap, unless remedied, will: (i) condemn many farmers in the Global South to live in poverty; and (ii) make them less competitive and force them to follow the well-established trend of exiting farming altogether, which (iii) will contribute to greater dependence on imported food in many countries.